2022
DOI: 10.1007/jhep09(2022)032
|View full text |Cite
|
Sign up to set email alerts
|

Spectral form factor of a quantum spin glass

Abstract: It is widely expected that systems which fully thermalize are chaotic in the sense of exhibiting random-matrix statistics of their energy level spacings, whereas integrable systems exhibit Poissonian statistics. In this paper, we investigate a third class: spin glasses. These systems are partially chaotic but do not achieve full thermalization due to large free energy barriers. We examine the level spacing statistics of a canonical infinite-range quantum spin glass, the quantum p-spherical model, using an anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…This enhancement shows up in realistic systems such as the Bunimovich stadium [58,59], which have different sectors of their Hamiltonian which behave differently under reflection symmetry. It has recently been shown [46] that at times sub-exponential in system size, all-to-all spin glasses exhibit an enhancement of the ramp equal to the number of effective "sectors", i.e., regions of configuration space rendered dynamically disconnected by large energy barriers. This work serves as an extension of that result for a toy model of spin glasses, going out to late times.…”
Section: Review Of the Spectral Form Factormentioning
confidence: 99%
See 2 more Smart Citations
“…This enhancement shows up in realistic systems such as the Bunimovich stadium [58,59], which have different sectors of their Hamiltonian which behave differently under reflection symmetry. It has recently been shown [46] that at times sub-exponential in system size, all-to-all spin glasses exhibit an enhancement of the ramp equal to the number of effective "sectors", i.e., regions of configuration space rendered dynamically disconnected by large energy barriers. This work serves as an extension of that result for a toy model of spin glasses, going out to late times.…”
Section: Review Of the Spectral Form Factormentioning
confidence: 99%
“…Motivated by our recent results for the early time ramp of the SFF for a quantum spin glass [46], we construct a minimal quantum model which can also exhibit glassy behavior. We create this model by generalizing the RP model examined in the previous section.…”
Section: The Block Rosenzweig-porter Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In chaotic systems, the SFF exhibits a dip-ramp-plateau structure (figure 1), while in integrable systems, the ramp is not present. It can be shown that in systems with conserved modes, or even slow modes or nearly conserved quantities, the ramp is significantly enhanced [4,[16][17][18].…”
Section: Random Matrices and Form Factorsmentioning
confidence: 99%
“…The inclusion of quantum fluctuations usually opens up a new route for thermalization in the equilibrium dynamics due to tunnelling between metastable states [21][22][23][24], even though counter-intuitive effects of quantum fluctuations inducing glassiness has been found in quantum quench protocols [25] or more recently in presence of more complex energy landscapes [26]. Within such a rich variety of phenomena, the recent theoretical [27][28][29][30][31] and experimental [32] observation of many-body chaos in quantum spin-glasses has drawn particular attention. Specifically, in Refs.…”
Section: Introductionmentioning
confidence: 99%